Comparative Analysis of Layer Thickness Measurement Methods for Photovoltaic Modules: A Comprehensive Study - Lukas Neumaier; Martin De Biasio; Anika Gassner; Gabriele C. Eder; Thomas Nigl (Advanced Energy & Sustainability Research)
The increasing volume of end‐of‐life (EoL) photovoltaic (PV) modules poses a significant challenge, necessitating efficient and sustainable recycling processes. In the PVReValue project, it is aimed to develop a comprehensive methodology for the systematic separation and recycling of EoL PV modules. Central to this effort is the precise determination of layer thicknesses, critical for effective characterization, and separation of input material. In this study, a comparative analysis of various industrial‐applicable methods is conducted for measuring layer thicknesses in PV modules. Both destructive and nondestructive techniques are evaluated based on criteria such as time, cost, accuracy, and applicability. Methods such as optical coherence tomography (OCT), coaxial multicolor confocal measurement, and ultrasonic measurements are assessed alongside traditional approaches like calotte grinding and optical 3D microscopy. In these findings, it is indicated that while OCT and confocal measurement offer high accuracy and nondestructiveness, they are complex and costly. Conversely, calotte grinding, although less costly, provides only localized information and can be challenging for polymers. In this study, it is concluded with recommendations for the possible integration of these methods into an industrial recycling workflow, highlighting the potential for improving PV module recycling efficiency and sustainability.